Diskursus Ekoteology Islam dalam Pengalaman Perlindungan Hutan Mangrove Bersama Komunitas Muslim di Seram Timur-Maluku - Saidin Ernas; Baco Sarluf; Muhammad Ipaloat (IAIN AMBON, 2023)
This paper is a development of a report on community service activities carried out with the Muslim community in the village of Geser Seram Timur-Maluku. Through the approach of